Участь перекладача у кримінальному процесі як гарантія забезпечення принципу мови судочинства - Кузик, Тарас Миронович; Kuzik, Taras (Одеса : Юрид. л-ра, 2012)
In the article the grounds of an interpreter's participation in criminal procedure on the basis of the new Criminal procedure code of Ukraine are analyzed. The content of the principle of language of criminal procedure is explored and a new version of the legal norm with this principle is offered.
Кузик Т. М. Участь перекладача у кримінальному процесі як гарантія забезпечення принципу мови судочинства / Т. М. Кузик // Актуальні проблеми держави і права : зб. наук. пр. / редкол.: С. В. Ківалов (голов. ред.), В. М. Дрьомін (заст. голов. ред.), Ю .П. Аленін [та ін.] ;МОНмолодьспорт України, НУ «ОЮА». – Одеса : Юрид. л-ра, 2012. – Вип. 67. - С. 714-721.
Keywords: мова, якою здійснюється кримінальне провадження; перекладач; неволодіння мовою кримінального провадження; недостатнє володіння мовою кримінального провадження; язык, на которым осуществляется уголовный процесс; невладение языком уголовного судопроизводства; недостаточное владение языком уголовного судопроизводства; language of criminal procedure; lack of knowledge of language of criminal procedure; insufficient knowledge of language of criminal procedure